2019
DOI: 10.1016/j.nicl.2019.101897
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing a perfusion-based periventricular small vessel region of interest

Abstract: The periventricular white matter (PVWM) is supplied by terminal distributions of small vessels and is particularly susceptible to developing white matter lesions (WML) associated with cerebral small vessel disease (CSVD). We obtained group-averaged cerebral blood flow (CBF) maps from Arterial Spin Labeled (ASL) perfusion MRI data obtained in 436 middle-aged (50.4 ± 3.5 years) subjects in the NHLBI CARDIA study and in 61 elderly (73.3 ± 6.9 years) cognitively normal subjects recruited from the Penn Alzheimer's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 66 publications
3
42
0
Order By: Relevance
“…Use of healthy subject DTI data with virtual lesions circumvented the challenges associated with performing DTI tractography in lesioned brains (24,25) and progressive ischemic PVWM lesions were simulated by varying the CBF threshold on a mean CBF map from a large cohort of middle-aged subjects, allowing the connectivity effects of PVWM lesions to be isolated from deep WM lesions that are typically seen clinically with advancing age and subcortical ischemic lesion burden. We showed that sub-threshold CBF recapitulates the pattern of PVWM lesion burden seen in an elderly cohort, as demonstrated in our prior work (28).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Use of healthy subject DTI data with virtual lesions circumvented the challenges associated with performing DTI tractography in lesioned brains (24,25) and progressive ischemic PVWM lesions were simulated by varying the CBF threshold on a mean CBF map from a large cohort of middle-aged subjects, allowing the connectivity effects of PVWM lesions to be isolated from deep WM lesions that are typically seen clinically with advancing age and subcortical ischemic lesion burden. We showed that sub-threshold CBF recapitulates the pattern of PVWM lesion burden seen in an elderly cohort, as demonstrated in our prior work (28).…”
Section: Discussionsupporting
confidence: 84%
“…Fig. 1B shows a map of cerebral blood flow (CBF) in standard space derived from arterial spin labeled perfusion MRI data in 436 middle aged subjects, as described in our prior work (28). This map has been overlaid onto the same slices shown in Fig.…”
Section: White Matter Lesion Frequency Versus Periventricular Cerebramentioning
confidence: 99%
See 2 more Smart Citations
“…Seven of the 27 newly identified cross-sectional studies investigated patients with cognitive impairment or dementia; including Alzheimer's disease (AD), 18,19 mild cognitive impairment (MCI) 8, 10, 20 and vascular cognitive impairment (VCI). 9,21 Thirteen of the 27 added cross-sectional studies investigated patients without cognitive impairment including patients with varying degrees of WMH burden, 7,16,22,23 hypertensive patients with and without SVD, 6,24,25 individuals with Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL), 26 cognitively normal older subjects 14,27 and patients with ischaemic stroke. 28 Two of these 13 studies investigated the effect of blood pressure reduction on CBF in SVD, from which only baseline data on CBF and WMH burden, prior to any treatment, were extracted.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%